Influência de lojas âncoras de experiência na performance financeira de shopping centers : um estudo multicaso - Lago, David Hunner Vieira do (My University, 2026)
Experience-anchor stores, mixed-use operations such as restaurants and entertainment venues, have increasingly been consolidated as strategies to expand visitor traffic, extend dwell time, and promote differentiated experiences in shopping centers. In this context, this research aims to analyze the influence of implementing experience-anchor stores on the financial performance of shopping centers through a multiple-case study using both qualitative and quantitative approaches. The topic becomes especially relevant in a context of retail transformation, driven by the rise of e-commerce, changes in consumer habits, and the need to reinvent physical shopping spaces. The methodology adopted includes the analysis of three Brazilian shopping center cases that incorporated experience anchors between 2018 and 2023. Secondary data were used, including financial reports, sales flow, rental income, and vacancy rates, as well as primary data obtained through semi-structured interviews with shopping center managers. The analysis of the results employs triangulation between qualitative and quantitative data, with software support. Preliminary findings indicate a real increase in sales and net growth in rental income above inflation rates, in addition to a positive reconfiguration of the tenant mix surrounding the new anchors. These findings show that experience anchors not only fulfill an attractive role, but also contribute to the economic sustainability of shopping centers. [resumo fornecido pelo autor]
As lojas âncoras de experiência, operações de uso misto como restaurantes e operações de entretenimento vêm se consolidando como estratégias para ampliar o fluxo de visitantes, prolongar o tempo de permanência e promover experiências diferenciadas em shopping centers. Nesse sentido, essa pesquisa tem como objetivo analisar a influência da implantação de lojas âncoras de experiência na performance financeira de shopping centers, a partir de um estudo multicaso com abordagem qualitativa e quantitativa. O tema ganha relevância em um contexto de transformação do varejo, impulsionado pela ascensão do e-commerce, pela mudança nos hábitos de consumo e pela necessidade de reinvenção dos espaços físicos de compra. A metodologia adotada contempla a análise de três casos de shopping centers brasileiros que incorporaram âncoras de experiência entre 2018 e 2023. Foram utilizados dados secundários (relatórios financeiros, fluxo de vendas, receita de aluguel, vacância) e dados primários obtidos por meio de entrevistas semiestruturadas com gestores dos shoppings. A análise dos resultados emprega triangulação entre dados qualitativos e quantitativos, com apoio dos softwares. Os resultados preliminares indicam incremento real nas vendas e crescimento líquido na receita de aluguel acima dos índices inflacionários, além da reconfiguração positiva do mix de lojas no entorno das novas âncoras. Esses achados evidenciam que as âncoras de experiência não apenas cumprem um papel atrativo, mas também contribuem para a sustentabilidade econômica dos shoppings. [resumo fornecido pelo autor]
Keywords: Administração; Centros comerciais; Lojas de departamentos; Consumidores; Comércio varejista; Management; Shopping centers; Department stores; Consumers; Retail trade